DIGITAL PAYMENT TRANSFORMATION IN THE PHILIPPINES: FROM CASH TO GCASH - Daniel Susilo; Carl C. G. Dizon (SEAN Institute, 2023)
This study examines the progression of digital payment systems in the Philippines, with a particular focus on the shift from traditional cash transactions to the adoption of GCash. The introduction underscores the significance of digital financial transactions within the contemporary economy, specifically emphasising the distinctive circumstances of the Philippines. The theoretical foundation is based on the Diffusion of Innovations hypothesis, which places emphasis on the process by which new technologies are embraced within communities. The methodology encompasses a comprehensive examination of existing scholarly literature, governmental publications, and industry analyses pertaining to digital payment systems and specifically GCash. The results indicate a notable transition towards digital payment methods, with a particular emphasis on GCash. This shift may be attributed primarily to the rise in smartphone usage, government-led efforts, and the demand for contactless transactions in response to the COVID-19 pandemic. The ensuing discourse provides a more comprehensive analysis of the obstacles and prospects within the realm of digital payments, including the issue of the digital divide and the possibilities for enhancing financial inclusivity. The study's findings indicate that the digital payment transformation has significant ramifications for the economy of the Philippines. It suggests that ongoing efforts are necessary to establish an inclusive digital financial ecosystem. These endeavours would entail the resolution of infrastructural deficiencies, enhancement of digital literacy, and execution of pertinent policies. This research study aims to enhance the comprehension of the process of digital payment transformation in developing nations, with a specific focus on the Philippines. It offers valuable insights that can be utilised by policymakers, financial institutions, and fintech startups.